(untitled) (Research, Society and Development, 2020)
This research is aimed to explain the process of victim’s losses recovery by the minor offences’ perpetrator using restorative justice approach. Restorative justice here means as the settlement effort through penal mediation. The method used in this research is juridical normative focused on library research based on the regulation and literatures dealing with the problem discussed. The results shows that the settlement of minor offences through restorative justice is need to be implemented to fulfill a sense of justice, legal certainty, and its usefulness for the society. By combining the restorative justice and quick inspection, then the restorative justice can be performed without involving public persecutor and detention process.